(untitled) (Research, Society and Development, 2022)
Seeds pathogens compromise the production of beans. Seed treatment is used to mitigate the pathogens’ incidence and damage; however, the forms of control must be efficient and safe. Our main hypothesis is that synthetic chemicals are the most efficient treatment against bean seed pathogens. Thus, we discuss the controls of pathogens in bean seeds using different treatments and identify the technologies studied for these purposes. This review assessed papers that used different strategies to control the bean seed pathogen. There are treatment classifications in which synthetic chemicals are the most efficient to control these pathogens, but as a burden, they pose a risk to human health, animals, and the environment. However, alternative, and complementary solutions to control these microorganisms have been sought in physical, natural, and biological control. Of the studies evaluated, 35.29% used biological control, 17.65% used control with natural agents, 11.76% used physical control, and the others corresponded to 5.88% each. 72.22% are related to the control of fungal pathogens, 16.67% to the control of bacteria, and only 11.11% to the virus. 94.12% were effective, and only 5.88% were not successful in controlling. Overall, our findings expand our knowledge about the alternative treatments that are efficient against pathogens associated with bean seeds which could serve as an alternative tool for plant disease management and seed treatment.